Buying center-selling center interaction as a driver for power dynamics in buyer-supplier relationships - Siemieniako, Dariusz; Makkonen, Hannu; Mitrega, Maciej (Elsevier, 2023)
The concept of power is an enduring topic in various domains of business-to-business literature. However, the extant research is scattered, and synthesizing approaches are largely missing. This study builds on the concepts of buying and selling center and integrates their inherent focus on individual actors with the conceptualizations of business relationships. The purpose is to increase understanding on buying center-selling center interaction as a driver for power dynamics in buyer-supplier relationships. By analyzing two international business relationships manifesting significant power dynamics, the study contributes by building towards synthesis between individual agents and business relationship concepts, and providing a nuanced and multi-layered approach to power dynamics in business relationships. We present an empirically enriched framework that articulates the key insights learnt from the study. The study provides tools for managers to visualize the threats and opportunities in terms of relationship power when managing key individuals in buyer-seller relationships.
Keywords: Buying center; Selling center; Buyer-supplier interaction; Buyer-supplier relationship; Power asymmetry; Power dynamics; fi=Markkinointi|en=Marketing|